Phenology of ectomycorrizal fungi in subtropical evergreen Castanopsis forest - Christensen, Morten (Botanica Orientalis: Journal of Plant Science, 2010)
The mycota of Himalaya is poorly described and information on the ecology of ecto-mycorrhizal species in the region is very limited. Three years (2004-2006) of intensive studies of the fruitbodies in Schima-Castanopsis forest in Central Nepal have documented a high diversity of ecto-mycorrhizal fungi. Systematic information collected from five forests in the surrounding of Pokhara are analyzed to describe the phenological patterns. The species diversity of fruitbodies is highest just after the first pre-monsoon rainfall in late May to early July and by the late monsoon rain of September and early October. Similar bimodular patterns are described from areas with warm humid climate in Japan. In cold Temperate and Boreal areas in Europe and North America as well as in the mountainous areas of Nepal only one peak of the ecto-mycorrhizal fungi is found. In these areas the temperature seems to be the main agent in determining the time of fructification of the ecto-mycorrhizal fungi. In contrast studies from Subtropical Mediterranean climate in Southern Europe with winter rain found fructification in the cold season, indicating that moisture is more crucial for the fruitbody creation than temperature in subtropical areas. Key-words: Central Nepal; ecto-mycorrhiza; Himalaya; Schima-Castanopsis forest. DOI: 10.3126/botor.v6i0.2904 Botanica Orientalis - Journal of Plant Science (2009) 6: 8-11